SISTEM INFORMASI TRANSFUSI DARAH BERBASIS WEB MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT - Nurrohman, Muhammad Yusuf; Hardiani, Tikaridha; Wijayanto, Danur (Jurusan Teknik Informatika Fakultas Teknik Universitas Trunojoyo Madura, 2024)
Blood Transfusion at RS PKU Muhammadiyah Gamping faces several issues in the management, administration, and reporting of medical record data, which are still conducted manually. In an effort to comply with the Indonesian Minister of Health Regulation No. 24 of 2022, which requires all healthcare facilities in Indonesia to implement Electronic Medical Records, a Blood Transfusion Information System has been developed. This system is designed to address the problem of medical record storage at RS PKU Muhammadiyah Gamping, which previously relied on paper records stored in file cabinets. The system development uses the Rapid Application Development (RAD) method, chosen for its ability to expedite the system development process. The RAD method involves sequential phases of analysis, design, development, and transition. This research aims to develop an information system that facilitates the administration and reporting of blood transfusions at RS PKU Muhammadiyah Gamping using the CodeIgniter Framework. The system aims to assist nurses in managing and reporting medical record data related to blood transfusions. Testing using the black-box method showed a 100% success rate, indicating excellent performance.Keywords:.Electronic Medical Records, Blood Transfusion Information System, RS PKU Muhammadiyah Gamping, RAD Method, CodeIgniter Framework